2018
DOI: 10.1111/jce.13487
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of pace mapping in catheter ablation of left ventricular papillary muscle ventricular arrhythmias with a preferential conduction

Abstract: When an M-PM with latency was recorded in LVPM VAs, RFCA at that site was highly successful. Attention should be paid to latency as well as the score during pace mapping of LVPM VAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 7 publications
1
34
0
Order By: Relevance
“…In some patients, the VA can originate in a deep intramural location, and the electrograms with the earliest activation time can have a far-field appearance or be difficult to define. In these patients, ablation at sites with a matching pace map and prolonged S-QRS might be successful, although longer and higher-powered RF application might be necessary ( S9.3.2.16 ).…”
Section: Mapping and Ablationmentioning
confidence: 99%
“…In some patients, the VA can originate in a deep intramural location, and the electrograms with the earliest activation time can have a far-field appearance or be difficult to define. In these patients, ablation at sites with a matching pace map and prolonged S-QRS might be successful, although longer and higher-powered RF application might be necessary ( S9.3.2.16 ).…”
Section: Mapping and Ablationmentioning
confidence: 99%
“…EUROPEAN JOURNAL OF ARRHYTHMIA & ELECTROPHYSIOLOGY activation map and when ablation at earliest activation sites fail. Good pace maps can be obtained at multiple sites remote to the earliest activation sites and ablation at these sites might be successful when VAs are not inducible 35. …”
mentioning
confidence: 99%
“…[19][20][26][27][28][31][32][33] Intracardiac echocardiography (ICE) was used to guide mapping and ablation in 19 studies (86.4%). [14][15][16][17][18][19][20][21][22][23][25][26][27][28][29][30][31][32][33] In 13 studies ICE assisted all procedures, [15][16][19][20][21][22][23]25,[28][29][30][31]33 whereas in six studies only a portion of the procedure was ICE-guided. 14,[17][18][26][27]32 Three dimensional electroanatomical mapping system assisted the procedure in all cases (Biosense Webster CARTO system in 16 studies, 14,[16][17]…”
Section: Study Selection and Patient Characteristicsmentioning
confidence: 99%
“…Access to the left ventricle was obtained through retrograde crossing the aortic valve in six studies [13][14][17][18]24,27 or trans-septal puncture in two studies. [19][20] In 10 studies both the approaches were used, 15,23,[25][26][28][29][30][31][32][33] and in three studies the approach used for mapping and ablating the PM-VAs was not reported. 16,[21][22] Mapping and ablation catheters features were reported in 95% of the studies (n = 20, Table 2).…”
Section: F I G U R E 2 Study Flow Diagrammentioning
confidence: 99%
See 1 more Smart Citation